Spurring innovation through global knowledge management at Procter & Gamble - Bjo?rkman, Ingmar; Evans, Paul; Pucik, Vladimir ([London] : SAGE, 2016)
Procter & Gamble is a manufacturing multinational company of consumer goods founded in Cincinnati, US. Since then, the firm has established a worldwide network of research centers and facilities, and developed new innovative products. Here, we examine an example of how knowledge and innovation is a vital aspect of management in multinational companies.
Originally Published in: Harzing, A. W., & Pinnington, A. (2011). Spurring Innovation through Global Knowledge Management at Procter & Gamble. In International human resource management (3rd ed., pp. 369-376). London: SAGE Publications Ltd. Print. ISBN: 9781847872937.
Description based on online resource; title from home page (viewed on April 21, 2016).
Keywords: elektronické knihy; electronic books; Procter & Gamble Company; Knowledge management -- Case studies; International business enterprises -- Information resources management -- Case studies